How Does AI Support Eating Disorder Treatment? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Eating disorders (EDs) are complex and serious psychiatric conditions that significantly impact physical and psychological health. They are associated with l...
Keywords: AI in Mental Health; Support; Eating; Disorder; Artificial Intelligence; Machine Learning; Healthcare